Transient global amnesia after clioquinol: five personal observations from outside Japan. Issue 12 (December 1979) - Mumenthaler, M; Kaeser, H E; Meyer, A; Hess, T
Abstract : Five personal observations of an acute amnestic episode in younger individuals after intake of clioquinol are described together with three observations from the medical literature. In five of these cases the episode began after an unusually large dose, in three after a therapeutic one with a latency of about 24 hours. The clinical aspect closely resembled classical transient global amnesia but the episode after clioquinol lasted longer (24 hours to three days) and a more or less extensive retrograde amnesia persisted permanently. In one patient after three tablets of Mexase a clioquinol concentration of 12 microgram/ml in plasma was found 24 hours after the specified dose, which is an unexpectedly high concentration compared to those reported as late as 24 hours after a single equal dose of Mexase or any other clioquinol-containing preparation. Another patient had a brief relapse two years after the first episode, after a single therapeutic dose of another clioquinol preparation.